Running on Empty: Of Hypopinealism and Human Seasonality - Kunz, Dieter; Wahnschaffe, Amely; Kaempfe, Nina; Mahlberg, Richard (Frontiers in Pharmacology, 2021)
The pineal hormone melatonin is the natural transducer of the environmental light–dark signal to the body. Although the responsiveness to photoperiod is well-conserved in humans, only about 25 percent of the human population experiences seasonal changes in behavior. As a consequence, humans seem to have adapted—at least partly—to the seasonal changes in day length. The aim of the study was to demonstrate that the individual melatonin deficit marker DOC (degree of pineal calcification) is related to variation of seasonal phenomena in humans. Out of 3,011 patients in which cranial computer tomography (cCT) was performed for diagnostic reasons, 97 consecutive “healthy” subjects (43 female, 54 male; age 18–68 yrs, mean ± SD: 35.0 ± 13.1) were included. Exclusion criteria were pathological finding in cCT, acute/chronic illness including alcohol/drug abuse, shift work, and medication, which are known to influence melatonin excretion. The degree of pineal calcification (DOC) was semiquantitatively determined using the previously validated method. The Seasonal Pattern Assessment Questionnaire (SPAQ) was performed in a telephone interview. Twenty-six subjects fulfilled the criteria for seasonal affective disorder (SAD) or subsyndromal (S) SAD. Seasonality was more pronounced in women than in men (SPAQ seasonality score: 7.8 ± 4.0 vs. 4.9 ± 4.5; p = 0.001) and negatively and significantly associated with age (r = −0.178; p = 0.04). The subjective sleep length significantly varied between seasons (one-way repeated measures ANOVA: F = 45.75; p < 0.0001), with sleep during winter being 53 min (±70 min) longer than during summer. Controlling for age, the total seasonality score was negatively and significantly associated with DOC (r94 = −0.214; p = 0.036). Data confirm earlier studies with respect to distribution of seasonality with sex and age. The survival of seasonality in the sleep length of people living in an urban environment underlines functionality of the circadian timing system in modern societies. Moreover, data confirm for the first time that diminished experience of seasonality in behavior is associated with a reduced individual capacity to produce melatonin.